Quinoline as a Privileged Structure: A Recent Update on Synthesis and Biological Activities - Kushwaha, Pragati (Current Topics in Medicinal Chemistry, 2024)
Among heterocyclic compounds, quinoline is one of the best ubiquitous heterocyclic rings for medicinal chemistry purposes. Quinoline appears to be a powerful chemical structure to develop new drug entities. The quinoline derivatives own a wide array of biological activities such as anticancer, antimalarial, antimicrobial, anti-inflammatory, anti-leishmanial, etc. Because of the wide spectrum of bioactivities, the scientific communities are still looking for more efficient synthetic routes to form quinoline derivatives. Therefore, the primary focus of this review is to provide a thorough and inclusive, updated report on quinoline analogs that may pave the way for more efficient drug development.
Keywords: Antimalarial